Emergence in Space Technologies with Nanosatellites, Exploring the Applications of AI in Space Development, and Future Trends - Paneru, Biplov; Paneru, Bishwash; Poudyal, Ramhari (Indonesian Journal Publisher, 2024)
Since, the first satellite was launched years ago, more than 6000 have been flown into orbit. Space science is the most fascinating field of study and research in the twenty-first century. The satellites are objects that travel in an elliptical orbit around the planet. Artificial satellites are being produced in large numbers. One of the most important aspects of modernizing science and communication technology, including space technology, mobile and radio communication, is satellite communication. The focus of the research work is on nanosatellites like cube sats, which are becoming increasingly well-known because to their wide-ranging applications in the field of radio transmission. This review paper explains some recent developments and the importance of nanosatellites in advancing space technology, highlight the recent development of space technologies in developing Asian nations and presents the future prospects of satellites development. Also, study is done in the role of AI in space technologies enhancement and space industries development its applications and future trends are discussed in this paper.